Clearance of primary necrotic cells by non-professional phagocytes - Schwegler, Manuela; Wirsing, Anna Maria; Dollinger, Alena J.; Abendroth, Benjamin; Putz, Florian; Fietkau, Rainer; Distel, Luitpold (Biology of the Cell, 2015)
Homotypic internalisation of tumour cells has frequently been observed in tumour tissue sections. Events of non-professional phagocytosis, however, may also occur in normal tissue if the number of dying cells exceeds the phagocytic capacity of professional phagocytes such as macrophages and dendritic cells. The aim of this study was to investigate the molecular background of non-professional phagocytosis of primary necrotic cells by neighbouring tumour cells and normal skin fibroblasts.We demonstrate that homotypic and heterotypic uptake of necrotic cells is a feature common to various cell types. Investigating critical stimuli of necrotic cell clearance we found that non-professional phagocytes require cytoskeleton rearrangement, recognition of phosphatidylserine and GTPase activity of dynamin II, which is normally engaged in endocytosis. Additionally, we have observed an accumulation of adhesion molecule E-cadherin, phosphorylated actin-linker protein ezrin, lysosomal-associated membrane protein 1 and microtubule-associated protein 1 light chain 3 at the site of engulfment. Loss of membrane integrity and an increase in the intracellular level of heat-shock protein 70 in the necrotic cells have also been observed.Our results shed light on the mechanism of necrotic cell removal by tumour cells and normal skin fibroblasts in vitro. It is reasonable to assume that this process has a physiological relevance in inflammation and autoimmune disease in normal tissue as well as in tumours regarding immune cell infiltration. We conclude that necrotic cell clearance by non-professional phagocytes contributes to the phagocytic activity by macrophages and that this process may prevent release of proinflammatory damage-associated molecular pattern molecules.
EVALuna2:18281